A metabonomic study on the urine of rowing athletes - Kang, Y.; Liu, C. (Exercise Biochemistry Review, 2018)
Objective To extract information that affect sport performance, the technique of urine metabolism and quantitative difference(QD)analysis were combined in search of the characteristic metabolites of the rowing athletes.